Impact on malaria parasite multiplication rates in infected volunteers of the protein-in-adjuvant vaccine AMA1-C1/Alhydrogel+CPG 7909. - Duncan, C; Sheehy, S; Ewer, K; Douglas, A; Collins, K; Halstead, F; Elias, S; Lillie, P; Rausch, K; Aebig, J; Miura, K; Edwards, N; et al. (Public Library of Science, 2011)
BACKGROUND: Inhibition of parasite growth is a major objective of blood-stage malaria vaccines. The in vitro assay of parasite growth inhibitory activity (GIA) is widely used as a surrogate marker for malaria vaccine efficacy in the down-selection of candidate blood-stage vaccines. Here we report the first study to examine the relationship between in vivo Plasmodium falciparum growth rates and in vitro GIA in humans experimentally infected with blood-stage malaria. METHODS: In this phase I/IIa open-label clinical trial five healthy malaria-naive volunteers were immunised with AMA1/C1-Alhydrogel+CPG 7909, and together with three unvaccinated controls were challenged by intravenous inoculation of P. falciparum infected erythrocytes. RESULTS: A significant correlation was observed between parasite multiplication rate in 48 hours (PMR) and both vaccine-induced growth-inhibitory activity (Pearson r = -0.93 [95% CI: -1.0, -0.27] P = 0.02) and AMA1 antibody titres in the vaccine group (Pearson r = -0.93 [95% CI: -0.99, -0.25] P = 0.02). However immunisation failed to reduce overall mean PMR in the vaccine group in comparison to the controls (vaccinee 16 fold [95% CI: 12, 22], control 17 fold [CI: 0, 65] P = 0.70). Therefore no impact on pre-patent period was observed (vaccine group median 8.5 days [range 7.5-9], control group median 9 days [range 7-9]). CONCLUSIONS: Despite the first observation in human experimental malaria infection of a significant association between vaccine-induced in vitro growth inhibitory activity and in vivo parasite multiplication rate, this did not translate into any observable clinically relevant vaccine effect in this small group of volunteers. TRIAL REGISTRATION: ClinicalTrials.gov [NCT00984763].